A novel silk/PES hybrid nanofibrous scaffold promotes the in vitro proliferation and differentiation of adipose‐derived mesenchymal stem cells into insulin producing cells. (24th March 2020) - Hosseini, Motaharesadat; Dadashi‐Noshahr, Karim; Islami, Maryam; Saburi, Ehsan; Nikpoor, Amin R.; Mellati, Amir; Mossahebi‐Mohammadi, Majid; Soleimanifar, Fatemeh; Enderami, Seyed E.
Abstract : Using stem cells to replace the lost beta cells is a hopeful strategy in the treatment of diabetic patients. Furthermore, during stem cell culture and therapy, it is a need to use a substrate to act as a supportive matrix to mimic 3D in vivo microenvironment. Therefore, in this study, human adipose‐derived stem cells were used to differentiate into insulin‐producing cells (IPCs) on a silk/polyethersulfone (PES) scaffold. After exposing to the differentiation media, 2D and 3D (silk/PES) cultured cells were gradually aggregated and formed spherical shaped clusters. The viability of cells was comparable in both 3D and 2D culture. As the results of gene expression assay in both RNA and protein level showed, the differentiation efficiency was higher in 3D culture. Furthermore, ELISA revealed that the release of C‐peptide and insulin was higher in 3D than 2D culture. It seems that silk/PES nanofibrous hybrid scaffold could provide an appropriate matrix to mimic in vivo microenvironment and therefore increases the IPC differentiation potency of stem cells.